Comment on “Molten Salt Synthesis of Bi2WO6 Powders and its Visible-Light Photocatalytic Activity” in Materials Research. 2019; 22(5): e20190311 - Landi Jr.,Salmon (2021)
Abstract Recently, Dai et al. published a paper in Research Materials 2019; 22(5): e20190311. They have investigated the visible-light photocatalytic activity of the synthesized Bi2WO6 powders1. In the context of determining of band gap energy based on diffuse reflectance measurements, the cited authors make some mistakes, which are clarified in the present letter.